Studies and applications of doppler effect for electron polarization and diagnostics of electron beams - Ivanov, B.I. (Вопросы атомной науки и техники, 2003)
The Doppler effect at the electron cyclotron resonance (ECR) was studied experimentally. Both a non-relativistic and a relativistic Doppler effect at ECR was detected. Using Doppler effect at ECR, it was developed the method of measuring the electron energy distribution function for electron beams with energies from non-relativistic to relativistic ones. Measurements were made for non-relativistic electron beams in case of three experimental schemes: close RF cavities, open microwave resonator, and propagation of microwaves in free space. A new method of polarization of free electrons was considered that based on the special mode of microwave pumping using Doppler effect at the electron spin resonance in an external uniform magnetic field.